An experimental study on thermophysical properties and heat transfer characteristics of low volume concentrations of Ag-water nanofluid. (May 2016) - Hemmat Esfe, Mohammad; Saedodin, Seyfolah; Biglari, Mojtaba; Rostamian, Hadi
Abstract: An experimental research has been conducted on low concentration of silver-water nanofluids through a straight tube for turbulent flow condition. This study aims at showing the impact of nanoparticle existence and volume concentration on thermal conductivity, dynamic viscosity, convective heat transfer characteristics, and pressure drop in turbulent flows regime. The findings showed that adding nanoparticles in the fluid and increasing Reynolds number bring about an increase in the Nusselt number in turbulent flow. When Reynolds number is approximately 22, 000 the Nusselt number increases by 11.8% at volume concentration of 1%. This value is 10.35% when Reynolds number is about 5100. Also, at 1% volume concentration, there is 15.75% (average) increase in pressure drop.